The Influence of Using the Educaplay Website on Increasing the Memorization Motivation of Students at the ITS PKU Muhammadiyah Surakarta Student Boarding School - Ramadhani Nur Hikmah; Mahasri Shobahiya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Formal education in Indonesia. In the context of Islamic education, Tahfidz is a mandatory subject in several Islamic-based schools and Islamic boarding schools. This research aims to find out the extent to which the use of the Educaplay website influences increasing the learning motivation of student students at the ITS PKU Muhammadiyah Surakarta Student Islamic Boarding School (Pesantren Mahasiswa). Educaplay is a web-based learning platform that offers various types of interactive media to support the learning process, such as quizzes, puzzles and other educational games. This research uses quantitative methods with a pre-experimental design and uses descriptive statistical analysis, involving a sample of Pesantren Mahasiswa ITS PKU Muhammdiyah Surakarta students. Data was collected through a questionnaire that measured the level of learning motivation after using Educaplay. The results of the research show that there is an increasing effect on students' learning motivation after using Educaplay, especially in terms of involvement and desire to learn more actively. Based on these findings, it can be concluded that the use of Educaplay has a positive impact on student motivation to study at Pesantren Mahasiswa ITS PKU Muhammadiyah Surakarta, so that it can be a more interesting and effective alternative learning method.